(untitled) (Journal of Science and Technology Research, 2022)
The present investigation was carried out to investigate the genetic variability, character association, correlation and path coefficient analysis among thirty accessions of sweet pepper. Significant variations were observed for different morphological traits, yield and yield attributes among the accessions studied. For all the characters, genotypic coefficient of variation (GCV) was smaller than phenotypic coefficient of variation (PCV). The highest genotypic and phenotypic coefficients of variations were recorded in case of number of fruit per plant (46.37 and 47.66%) followed by fruit yield per plant (39.39 and 41.44%), fruit length (31.92 and 32.48%) and dry weight (31.50 and 32.00%). Correlation coefficient study indicated that fruit yield had highly significant and positive correlation with individual fruit weight (r = 0.619) and number of fruit per plant (r = 0.605). In respect of path analysis, number of fruit per plant was contributed by maximum direct effect on sweet pepper (0.603) indicating its importance as a selection parameter. J. of Sci. and Tech. Res. 3(1): 95-102, 2021